Impact of Entrepreneurship Education on Attitudes of Students Towards Entrepreneurship - Muhammad Kashif Yaqub; Nadeem Ahmad Mufti; Shaukat Ali; Muhammad Uzair Khaleeq (Journal of Basic & Applied Sciences, 2015)
Entrepreneurship has become an international interest of students. The economic and social relevance of entrepreneurship is established across the world and many offerings are available by the universities. This has resulted into an increased focus of university teachers on entrepreneurship and entrepreneurial activities. The purpose of this paper is to study and evaluate the impact of entrepreneurship education on attitude of students to become an entrepreneur. Relationship between the education and student in development of entrepreneurial attitude is proposed.Review of the literature also shows the importance of entrepreneurship education in development of entrepreneurial attitude. This study was carried out in universities of Pakistan and data was collected from 10 different universities in which entrepreneurship is available as a course or discipline. Sample of 329 students was collected and statistical tests were used to evaluate the relationship. It is found that a strong relationship and positive correlation exist between attitude towards entrepreneurship and entrepreneurship education.